2018
DOI: 10.1007/s11892-018-1010-8
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Kidney Disease-Induced Insulin Resistance: Current State of the Field

Abstract: Recent mechanisms have been identified including SIRPα and specific E3 ubiquitin ligases causing insulin resistance in CKD. The hallmark finding in these mechanisms is degradation of the insulin receptor substrate 1 (IRS1) which impairs intracellular insulin signaling and ultimately metabolism. The mechanisms responsible for insulin resistance in CKD include inflammation, oxidative stress, elevations in aldosterone, angiotensin II, uremic toxins, and metabolic acidosis. Potential treatments currently available… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 63 publications
0
20
0
Order By: Relevance
“…High calorie dietary habits coupled with low levels of physical activity are the primary cause of metabolic syndrome in today’s world. IR is a key risk factor in the pathogenesis of various chronic diseases, including T2DM, chronic kidney disease and cognitive disorders [19,20,21]. Natural products are thought to be important sources for anti-T2DM drug discovery [22].…”
Section: Discussionmentioning
confidence: 99%
“…High calorie dietary habits coupled with low levels of physical activity are the primary cause of metabolic syndrome in today’s world. IR is a key risk factor in the pathogenesis of various chronic diseases, including T2DM, chronic kidney disease and cognitive disorders [19,20,21]. Natural products are thought to be important sources for anti-T2DM drug discovery [22].…”
Section: Discussionmentioning
confidence: 99%
“…[40][41][42] On the other side, some studies also observed increased IR states could be regulated via overactivated inflammatory response in the patients with CKD. [43][44][45][46][47] These results suggested there might be an internal relationship between IR and mildly decreased eGFR. For now, there were few studies focused on the mild decline of eGFR, but some results from CKD could indirectly confirm our conclusion.…”
Section: Open Accessmentioning
confidence: 99%
“…On the other hand, insulin resistance develops in patients with renal failure. 16 It is thought that insulin resistance also contributed to the etiopathogenesis of diabetes in our patient, who was obese and had renal dysfunction.…”
Section: Discussionmentioning
confidence: 70%